Engineering Asset Management 2016 Proceedings of the 11th World Congress on Engineering Asset Management (Lecture Notes in Mechanical Engineering,, 2018)
These proceedings gather selected peer-reviewed papers from the 11th World Congress on Engineering Asset Management (WCEAM), which was held in Jiuzhaigou, China, on 25-28 July, 2016. These proceedings cover a wide range of topics in engineering asset management, including: · strategic asset management; · condition monitoring and diagnostics; · integrated intelligent maintenance; · sensors and devices; · information quality and management; · sustainability in asset management; · asset performance and knowledge management; · data mining and AI techniques in asset management; · engineering standards; and · education in engineering asset management. The breadth and depth of these state-of-the-art, comprehensive proceedings make them an excellent resource for asset management practitioners, researchers and academics, as well as undergraduate and postgraduate students.